SISTEM INFORMASI PERUMAHAN PURIMAS CITRA GEMILANG 2 BERBASIS MOBILE - Arya Gemilang Deva Purwanto; Zainudin Zukhri (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
The development of information technology is increasing rapidly. Such developments affect the speed of obtaining information. Unfortunately, there are still many needs for good and comfortable housing that has not used a good information system to facilitate housing management and data collection such as in Purimas Citra Gemilang 2 Housing, a housing that has facilities to meet the needs of its residents. In managing housing, there are often obstacles in terms of data collection management such as monthly contribution payments, registration of prospective new residents, and recording of housing residents. This is because the recording is still manual. The use of technology, especially mobile-based applications, can optimize housing implementation by providing an integrated data management system that can be accessed via smartphones. Modern housing needs an application that can support the population system. On that basis, it is hoped that the application "Housing Information System Purimas Citra Gemilang 2 Based on Mobile", can help manage housing more efficiently and effectively. The app's features are for managing homeowner data, monthly dues payments, and social activities. The stages in the design of this system are analysis, design, implementation and testing. The waterfall method is used in the design of a housing data collection information system. Housing residents can use this system as a means of communication between officers and residents and to assist housing managers in carrying out social activities and housing data collection.